2017
DOI: 10.3892/mmr.2017.7436
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase is involved in synovial hyperplasia and angiogenesis in rats with collagen-induced arthritis

Abstract: Lysyl oxidase (LOX) serves an important role in remodeling the extracellular matrix and angiogenesis in various types of cancer; however, whether LOX is involved in the pathogenesis of rheumatoid arthritis remains unknown. In order to investigate this in the present study, β-aminopropionitrile, an inhibitor of LOX, was injected intraperitoneally into rats with type II collagen-induced arthritis (CIA). Subsequently, synovial hyperplasia was examined by hematoxyl in and eosin staining, and the microvascular dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Additionally, our previous study on rheumatoid arthritis also found that LOX expression levels in synovial fluid were positively correlated with the expression levels of MMP-2 and MMP-9. Inhibition of LOX expression in rat synovial fluid can downregulate MMP-2 and MMP-9 expression levels15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our previous study on rheumatoid arthritis also found that LOX expression levels in synovial fluid were positively correlated with the expression levels of MMP-2 and MMP-9. Inhibition of LOX expression in rat synovial fluid can downregulate MMP-2 and MMP-9 expression levels15.…”
Section: Discussionmentioning
confidence: 99%
“…However, our previous study found that expression of LOX and MMP-2 are positively correlated in gastric cancer tissues, and they play synergistic roles in promoting the invasion and metastasis of gastric cancer14. Another of our previous studies, on rheumatoid arthritis, found that inhibition of LOX expression in rat synovial fluid can downregulate MMP-2 and MMP-9 expression15. The relationship between LOX and MMP-2 and MMP-9 in tumorigenesis and tumor progression are still unclear.…”
Section: Introductionmentioning
confidence: 96%
“…Other evidence points to the involvement of lysyl oxidase (LOX) in the promotion of synovial hyperplasia and angiogenesis in CIA rats [ 43 ]. In this study, the researchers identified higher amounts of rough synovial membranes, higher microvascular density in those membranes and more synovial cell layers in CIA rats compared with saline-treated controls.…”
Section: Other Potentially Targetable Factors That Participate Inmentioning
confidence: 99%
“…In our previous study ( 17 ), the type II collagen-induced arthritis model of rats were established. BAPN was intraperitoneally injected to inhibit LOX activity.…”
Section: Discussionmentioning
confidence: 99%
“…The lysyl oxidase inhibitor β-aminopropionitrile (BAPN) impedes tumor angiogenesis and glioblastoma multiforme development in a mouse orthotopic brain tumor model ( 16 ). A previous study of our group indicated that inhibition of LOX attenuated the microvascular density in the synovial membranes of collagen-induced arthritis rats ( 17 ). In the present study we found that BAPN inhibited angiogenesis and migration of human umbilical vein endothelial cells (HUVECs).…”
Section: Introductionmentioning
confidence: 92%